2011
DOI: 10.1143/jjap.50.05ea04
|View full text |Cite
|
Sign up to set email alerts
|

New Copper Alloy, Cu(SnNx), Films Suitable for More Thermally Stable, Electrically Reliable Interconnects and Lower-Leakage Current Capacitors

Abstract: The Cu(SnN x ) alloy film formed in this study by doping a minute amount of Sn or SnN in a copper film via barrier-free Cu metallization method exhibits a good stability at high temperatures, an apparent improvement in adhesion and a greater electrical reliability, including low resistivity, lower leakage current in Cu(SnN x )-gate metal–oxide–semiconductor (MOS) capacitors, a longer time-dependent dielectric breakdown (TDDB) lifetim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2012
2012
2013
2013

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…4,5) While barrierless metallization simplifies the manufacture process and, hence, lowers manufacture costs of electronic devices, Cu alloy films also possess enhanced thermal stability due to the insoluble ingredient within the alloy (e.g., W), 6) which forms distinct microstructures and renders good thermal properties crucial to materials science. Previous studies [6][7][8][9][10][11][12][13][14][15][16] have shown that Cu(ReN) 10) alloy films are thermally stable up to 730 C. Transition metal nitrides have also received considerable attentions owing to their special properties and many technological applications. Recently, Ir nitrides have been successfully synthesized under high pressures and temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…4,5) While barrierless metallization simplifies the manufacture process and, hence, lowers manufacture costs of electronic devices, Cu alloy films also possess enhanced thermal stability due to the insoluble ingredient within the alloy (e.g., W), 6) which forms distinct microstructures and renders good thermal properties crucial to materials science. Previous studies [6][7][8][9][10][11][12][13][14][15][16] have shown that Cu(ReN) 10) alloy films are thermally stable up to 730 C. Transition metal nitrides have also received considerable attentions owing to their special properties and many technological applications. Recently, Ir nitrides have been successfully synthesized under high pressures and temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the alloying of Cu with insoluble components has attracted several major applications and is crucial in materials science. Previous studies [6][7][8][9][10][11][12][13][14][15][16] have shown that Cu(ReN) 9) alloy films are thermally stable up to 730 C. Transition metal nitrides have also received great attention for their constructive properties and many technical applications. Koike and colleagues also developed Cu-Mn alloy films that were applied to interconnects in semiconductor manufacture.…”
Section: Introductionmentioning
confidence: 99%
“…Hence, the alloying of Cu with insoluble components has attracted several major applications and is crucial in materials science. Previous studies [5][6][7][8][9][10][11][12][13][14][15][16][17] have shown that Cu(ReN) 12) alloy films are thermally stable up to 730 C. Transition metal nitrides have also received great attention for their desirable properties and in many technical applications. Lin et al also developed Cu-Ir alloy films that were applied to interconnects in semiconductor manufacturing.…”
Section: Introductionmentioning
confidence: 99%